Summary Note on Technical Assistance Provided in Support of the Greater Harare Water and Sanitation Strategic Plan - World Bank (World Bank, Washington, DC, 2016)
The severe conditions in Zimbabwe, which reached a nadir in 2008 and 2009, led to a collapse of basic systems including the reliability and safety of water supply and sanitation services, leading to an outbreak of cholera with more than 4,000 deaths and over 90,000 people infected. The World Bank provided Technical Assistance (TA) to the City of Harare to improve water and sanitation services in the period October 2012 to June 2014 to the value of approximately 600,000 US dollars. This Summary Note summarizes the key elements of the work undertaken and makes a set of recommendations to the City of Harare, the adjacent local authorities of Chitungwiza, Epworth, Norton and Ruwa, and Government of Zimbabwe to inform a strategic plan to improve water and Sanitation services in the greater Harare area. This Summary Note also sets out the context at the commencement of the TA, summarizes the work undertaken in the TA and the outcomes from this work, and makes recommendations for the way forward.